DO TENNIS PLAYERS LIVE LONGER? THE POSITIVE IMPACT OF TENNIS ON HEALTH - Magdalena Michalik; Magdalena Mida; Urszula Majda; Anna Maruszak; Julia Kwiecień; Julia Stołtny; Justyna Goryczka; Magdalena Lisik; Witold Kimla; Natalia Hajok (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: It is well known that physical activity has a positive impact on health.  It is important to note that the more time spent active, the lower the risk of all-cause mortality will be. Tennis is one of the world's most popular sports and has numerous health benefits, including the potential to increase lifespan. Its stand-out feature is its versatility of movement, with the potential to lead to longevity.Objective: Our aim is to demonstrate the connection between the longevity of tennis players and the many health benefits of playing this sport, and to promote physical activity in general.Material and methods: The study is founded on a multitude of analyses from 1980 to 2024, which were searched for on PubMed and Google Scholar. It is also supplemented with the most recent guidelines and the researchers' personal insights.Results: Tennis players seem to have the longest life expectancy of all athletes. This dependence is complex and multifactorial, but playing tennis certainly helps to avoid cardiovascular risk factors and improve quality of life and life expectancy. It prevents obesity and other components of metabolic syndrome, as well as osteoporosis. It also improves mental health, helping players to cope with stress.Conclusion: Tennis is definitely beneficial for physical and mental well-being. Playing this sport can help maintain good lifelong health and lead to longevity, so it is important to promote raquet sports.